Do Intrinsic And Extrinsic Motivation Really Affect On Interest To Become A Social Entrepreneur - Moses Lorensius Parlinggoman Hutabarat; Juan Stanley Davin Wijaya (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
The aim of this study was to investigate how different factors such as intrinsic motivation, extrinsic motivation, complex motivation, employment status, and startup capital affect the level of interest in becoming a social entrepreneur. A social entrepreneur is someone who creates a product or idea to help people who are facing challenges. While social entrepreneurship is a growing trend in Indonesia, the factors that drive entrepreneurs to become social entrepreneurs have not been extensively studied. This research was conducted using an associative approach and analyzed the data using the PLS-SEM method. The study surveyed 170 participants using a non-probability sampling technique and an online questionnaire. The findings showed that intrinsic motivation, employment status, and startup capital had a positive impact on the interest in becoming a social entrepreneur, whereas extrinsic and complex motivation did not have a significant effect.